Concomitant rectal and uterovaginal prolapse in the community - Rana, A.; Gurung, G.; Bista, K.D.; Amatya, A.; Joshi, A.B.; Sayami, J.; Shrestha, M.L.; Mishra, P. (Journal of Institute of Medicine Nepal, 2007)
Introduction: Concurrent occurrence of rectal and uterovaginal prolapse in many women living in the community with misery should be made aware that there is possible solution to this dual debilitating condition by surgical correction which can be acquired at the same sitting to bring changes in their quality of life. Case report: We report here two cases of concomitant rectal and uterovaginal prolapse. Journal of Institute of Medicine Vol.28(1) 2006